The Effects of the COVID-19 Pandemic on Undergraduate Students’ Stress and Anxiety in a University in the UAE - Alfalasi, Khulood (2021)
Education has faced a significant transition in the 21st century, shifting from face-to-face classes to online classes due to the unprecedented COVID-19 pandemic. The pandemic's consequences have affected teaching and learning and negatively influenced students' psychological well-being. The following abstract will mention the aim and rationale of the study, the key theories involved, the method used, the study's key findings, implications, limitations, recommendations, and conclusion. This study aims to explore the pandemic's impact on undergraduate students' academic stress, especially as related to their academic performance. Furthermore, the students' coping strategies during the pandemic, if any, are investigated. The rationale of the study is to help students who are stressed and anxious by understanding the causes of stress and choosing suitable methods for supporting them emotionally, psychologically, and academically. The main theories used in the study includes demand-and-control theory, cognitive-mediational theory, the Ryff Scales of Psychological Well-Being, General Adaptation Syndrome (GAS), Hans Selye's theory of stress, academic self-efficacy, internal attribution of failure, self-determination theory (SDT), well-being theory, and Maslow's hierarchy of needs. The key theories explain how humans are influenced by their inner selves and their surroundings, specifically in terms of well-being, stress, anxiety, and motivation. They can be applied to students in education during a change in their environment, such as the COVID-19 pandemic. Moreover, the researcher used a mixed-method approach consisting of quantitative and qualitative data. Quantitative data collection was done by surveying 191 participants from the College of Education (COE) and students from other colleges enrolled in elective courses in the COE. The qualitative data collection was achieved through a focus group discussion with seven COE undergraduate students doing their internship. To analyze the survey's responses, the researcher used statistical methods of descriptive analysis, t-test, analysis of variance (ANOVA), and correlation. The focus group qualitative data was analyzed using thematic analysis to fill the gaps in the quantitative data. The key findings showed that the xenophobia factor (the fear of strangers) causes the highest stress levels, and students reported that workload and time constraint factors were top stressors. Also, A-range students (students with a GPA of 3.7 and above) were generally significantly less stressed than B-range students (GPA of 2.7–3.3). First-year students were significantly more stressed than second-year, third-year, and fourth-year students. It was found that internship students expressed their stress and anxiety due to the change to online education caused by the pandemic. The implications of the current study will allow educators and psychologists to better understand students' needs and apply effective techniques during the pandemic. The limitation of the study is that the number of participants could have been increased, especially in the focus group. Also, the focus group deals with the experience of internship students teaching online in public schools during the pandemic. It is not necessarily applicable to the 191 students surveyed in the questionnaire about their experience of studying online during the pandemic. The recommendation of this study is to increase the number of participants and improve the instruments. In conclusion, the researcher expected that the COVID-19 pandemic would directly impact student academic stress, but the findings slightly contradict the researcher's assumption. This study argues and claims that the COVID-19 pandemic did not have a direct impact as an epidemic on student academic stress. However, the changes caused by the COVID-19 pandemic in online education might cause students stress and anxiety; the study needs further research to confirm the argument.